Cefiderocol-Resistant Elizabethkingia anophelis Bacteremia Following WATCHMAN Implantation: A Case Report and Review of the Literature - Anna DeFrank; Michael Bosco; Sigridh Muñoz Gómez; Amit Dhaliwal (Case Reports in Infectious Diseases)
Elizabethkingia anophelis is an emerging pathogen associated with nosocomial and community outbreaks. Treatment of infection caused by E. anophelis is not well-defined given its extensive drug resistance profile, and infection carries a poor prognosis. E. anophelis is intrinsically resistant to many classes of antibiotics including carbapenems and polymyxins due to multiple resistance genes. Resistance to novel β-lactam/β-lactamase inhibitors has also been reported. The activity of cefiderocol (FDC) is unknown. Here, we describe a case of FDC-resistant E. anophelis bacteremia following WATCHMAN implantation. To our knowledge, this is the first reported case of FDC resistance amongst Elizabethkingia spp.